Model Pengendalian Fluktuasi Harga Gula Pasir dengan Program Stabilisasi dan Sokongan Harga Pemerintah - Burhan Burhan (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
White sugar is an important commodity Indonesia. Sugar’s price fluctuates due to itsavailability. The availability is depend on the season of sugar crop. Government has to controlits price to fullfill national price. However, previous experience shows that scarcity of productavailability and fluctuated of price due to unbalanced supply and demand quantity. This paperproposed a model to control price of white sugar for case of one commodity and multi region.One time horizon is divided into four periods: (i) beginning of harvesting period, (ii) end ofharvesting period, (iii) beginning of planting period, and (iv) end of planting period. There aretwo type of region considered (i) deficit region and (ii) surplus region. A price band isdetermined to define maximum and minimum price of white sugar. The government has twopolicy options to control the price of white sugar (i) price support program, and (ii) pricestabilization program. This problem is modeled as mathematical programming problem withobjective function is to maximize total benefit of producer, consumer, and government.Numerical example is provided to illustrate model mechanism for price of white sugar in bothregion.